Comparative Transcriptome and Endophytic Bacterial Community Analysis of Morchella conica SH - Lü, Bei B.; Wu, Guo G.; Sun, Yu; Zhang, Liang S.; Wu, Xiao; Jiang, Wei; Li, Peng; Huang, Yan N.; Wang, Jin B.; Zhao, Yong C.; Liu, Hua; Song, Li L.; et al. (Frontiers in Microbiology, 2021)
The precious rare edible fungus Morchella conica is popular worldwide for its rich nutrition, savory flavor, and varieties of bioactive components. Due to its high commercial, nutritional, and medicinal value, it has always been a hot spot. However, the molecular mechanism and endophytic bacterial communities in M. conica were poorly understood. In this study, we sequenced, assembled, and analyzed the genome of M. conica SH. Transcriptome analysis reveals significant differences between the mycelia and fruiting body. As shown in this study, 1,329 and 2,796 genes were specifically expressed in the mycelia and fruiting body, respectively. The Gene Ontology (GO) enrichment showed that RNA polymerase II transcription activity-related genes were enriched in the mycelium-specific gene cluster, and nucleotide binding-related genes were enriched in the fruiting body-specific gene cluster. Further analysis of differentially expressed genes in different development stages resulted in finding two groups with distinct expression patterns. Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway enrichment displays that glycan degradation and ABC transporters were enriched in the group 1 with low expressed level in the mycelia, while taurine and hypotaurine metabolismand tyrosine metabolism-related genes were significantly enriched in the group 2 with high expressed level in mycelia. Moreover, a dynamic shift of bacterial communities in the developing fruiting body was detected by 16S rRNA sequencing, and co-expression analysis suggested that bacterial communities might play an important role in regulating gene expression. Taken together, our study provided a better understanding of the molecular biology of M. conica SH and direction for future research on artificial cultivation.